2020
DOI: 10.1111/bcp.14164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the pharmacist‐led intervention on the control of medical cardiovascular risk factors for the primary prevention of cardiovascular disease in general practice: A systematic review and meta‐analysis of randomised controlled trials

Abstract: Aims:To conduct a systematic review and meta-analysis of the effectiveness of general practice-based pharmacist interventions in reducing the medical risk factors for the primary prevention of cardiovascular events. Methods:A systemic search was undertaken in 8 databases: PubMed, MEDLINE, EMBAS, PsycINFO, Cochrane Library, CINAHL Plus, SCOPUS and Science Citation Index, with no start date up to 27 March 2019. Randomised controlled trials assessing the effectiveness of pharmacist-led interventions delivered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 39 publications
1
37
0
4
Order By: Relevance
“…In addition to pharmacist role in optimising the use of medicines in liaison with GPs, providing advice about safe and effective use of medicines when dispensing to patients with prescriptions for the treatment of diabetes, heart disease and hypertension and thus relieving the pressure on the GP practices and A&E. Furthermore, pharmacists work directly in general practice as part of the multi-disciplinary team, in patient facing roles when managing conditions such as diabetes and hypertension [ 13 ]. A recent systematic review and meta-analysis which included 21 RCTs (8933 patients) showed that pharmacists-led interventions, as part of a team in general practice, can significantly reduce medical risk factors of CVD events when managing patients with hypertension, diabetes and dyslipidaemia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pharmacist role in optimising the use of medicines in liaison with GPs, providing advice about safe and effective use of medicines when dispensing to patients with prescriptions for the treatment of diabetes, heart disease and hypertension and thus relieving the pressure on the GP practices and A&E. Furthermore, pharmacists work directly in general practice as part of the multi-disciplinary team, in patient facing roles when managing conditions such as diabetes and hypertension [ 13 ]. A recent systematic review and meta-analysis which included 21 RCTs (8933 patients) showed that pharmacists-led interventions, as part of a team in general practice, can significantly reduce medical risk factors of CVD events when managing patients with hypertension, diabetes and dyslipidaemia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacists have been shown to support medication reconciliation and adherence, which can improve chronic disease management. [20][21][22][23][24] Retinal screening in people with diabetes can be done using remote technology at an optometrist's office, with data being analysed off-site by trained ophthalmologists. 25 Technology, including wearable devices like portable oxygen saturation monitors and home blood pressure monitors that connect to electronic medical records, may also partially fill in portions of the clinical exam.…”
Section: Challenges To Making Virtual Care the Central Solutionmentioning
confidence: 99%
“…[1] Many studies have con rmed that pharmacists' direct intervention or participation in multidisciplinary management teams can improve the clinical outcome and quality of life of patients by optimizing the use of drugs in different disease processes. [2][3][4][5][6][7][8][9] As a member of a multidisciplinary management team, pharmacists make full use of their professional knowledge and clinical experience to perform an important role in the care of intensive care unit (ICU) patients. [10] A previous systematic review su ciently dissected the impact on patient outcomes of pharmacist participation in multidisciplinary critical care teams.…”
Section: Introductionmentioning
confidence: 99%